Obtenção de nanomateriais de celulose contendo lignina residual a partir da madeira de seringueira e sua aplicação em filmes nanocompósitos com caseína - Silva, Maycon Jhony (2023)
In light of the escalating global population and the mounting environmental concerns, the quest for sustainable and renewable solutions has emerged as a paramount focus in scientific exploration across diverse fields. Plant-derived fibers stand out as a compelling sustainable option for fabricating materials due to their intriguing physical and mechanical attributes. Within this context, this study aimed to optimize the production of cellulose nanomaterials featuring varying lignin concentrations sourced from rubber tree wood fibers, and to explore their application in nanocomposite films. In the initial phase, fibers with distinct lignin compositions (15.3%, 6.7%, and 3.1%) underwent acid hydrolysis at differing reaction durations (45 minutes, 75 minutes, and 120 minutes) to yield cellulose nanomaterials with residual lignin (LCNCs). Subsequently, the study assessed the impact of integrating LCNCs, possessing both higher and lower lignin contents, along with commercially available cellulose nanocrystals (CNCs), into a casein (CA) matrix. The chemical treatments demonstrated remarkable efficacy, resulting in LCNCs with an average diameter below 4.1 nm, showcasing a high Crystallinity Index (I.C. > 70%), and achieving a reaction yield surpassing 50% across all evaluated reaction durations. Additionally, LCNCs exhibiting higher lignin content displayed notable colloidal stability (> -40.0 mV). The resultant nanocomposite films exhibited a superior I.C. compared to the pure CA matrix (34%), presenting as transparent, uniform, and easily manipulable films. The incorporation of LCNCs amplified the contact angle (θ >82.5°), enhancing the films' hydrophobic characteristics. Furthermore, films integrated with commercial CNCs and LCNCs with elevated lignin content exhibited a significant increase (p<0.05) of approximately 45% and 40%, respectively, in tensile strength (TS). Additionally, there was a 20% and 23% enhancement in the modulus of elasticity (EM) compared to the pure CA matrix. This research delineated a precise methodology for producing lignin-infused cellulose nanomaterials, promisingly valorizing rubber tree biomass residues. Moreover, it underscored the potential of integrating these materials into the casein matrix, yielding films endowed with exceptional properties, thus fostering diverse applications.